DECRIPTIVE ANALYSIS OF LOCAL WISDOM OF BATAK NARAJA IN IMPROVING TEACHER HOSPITALITY AT SMP NEGERI 1 SIANTAR NARUMONDA - Roy Siagian; Syawal Gultom; Rosnelli; Yuniarto Mudjisusatyo; Aman Simare-Mare; Arif Rahman (RADJA PUBLIKA, 2025)
Batak king is wisdom local and philosophy Toba Batak tribe in Toba Regency. Research It is very important for teachers to reflect mark Batak Naraja philosophy in learning. One of them relative teacher friendliness Still need improved. Because based on results observation and questionnaire beginning, there is some teachers have not understand mark Batak Naraja philosophy which has an impact to lack of teacher friendliness in learning. This is influence results Study students and teacher performance in the classroom. For that, it is necessary improvement understanding about Batak Naraja and its application in learning. Batak Naraja Indicators that want to improved is mark friendliness that is caring and wise. Method qualitative used​ is questionnaire and observation. The results in study This is the teacher experiencing improvement understanding about Batak Naraja which influences increasing mark teacher friendliness in learning. With thus need existence planting mark wisdom local Batak Naraja in education in a way sustainable.